UJI KUANTITATIF ASAM PADA MEDIA FERMENTASI LIMBAH TAHU MENGGUNAKAN BACILLUS SUBTILIS - ADRIANTO PRIHARTANTYO (LP2MTBM MAKARIOZ, 2020)
This study aimed to determine the acid levels produced in fermented liquid tofu waste using Bacillus subtilis quantitatively.This study began by growing Bacillus subtilis on LB (lactose Broth) media as a positive control and for negative control on LBmedium with variations of 1: 1 and 1: 3 for LB and tofu waste media and liquid tofu waste media only. In the beginning, liquidtofu had already had an acidic level due to the use of acetic acid as a clot. For this reason, it was carried out to check theacid level with the titration process first. Measurement of acid levels for fermentation results is carried out using titration. Inthis experiment, the bacteria growth, specific growth rate and reduction rate of reducing sugars from each of the four mediawere used. Measurement of growth and reducing sugar using a spectrophotometer. From the results of data processing, itwas found that acid concentration increased from the beginning before fermentation and after fermentation. In tofu wastemedia, acid concentration increased from 1.3M to 1.7M; tofu waste compared to LB 1: 3 from 1M to 1.3M; the tofu wastecompared to LB 1:1 from 0.85M to 1.1M and LB media from 0.5M to 0.6M. From these results, it can be seen that the highestincrease in acid concentration is found in tofu waste media.